Certified Beef Programs: What's in a Name? - Tracy Scheffler; Jason Scheffler; Chad Carr (EDIS, 2021)
This publication discusses certified beef programs and carcass quality specifications. Written by Tracy Scheffler, Jason Scheffler, and Chad Carr, and published by the UF/IFAS Department of Animal Sciences, October 2021.